The Contribution of the Madrasah Committee to Improving Teacher Performance: A Case Study at MI Tarbiyatussibyan, Temanggung - Nuryanto, Nuryanto; Muntaqo, Lutfan; Muntaqo, Rifqi; Sukawi, Z; Firdaus, Firdaus; Larasati, Almira (Journal of Education Technology and Inovation, 2025)
Teachers play a crucial role in achieving educational goals, as they directly interact with students in the teaching and learning process. Regardless of how advanced the curriculum, facilities, or technology are, their effectiveness depends on teachers’ ability to implement them. Therefore, analyzing teacher performance is fundamental to achieving the educational process standards. This study aims to: (1) examine teacher performance at MI Tarbiyatusshibyan, Kebumen, Pringsurat Subdistrict, Temanggung Regency in 2023; (2) investigate the roles and functions of the Madrasah Committee at the same school; and (3) assess the influence of the Madrasah Committee’s roles and functions on teacher performance. A qualitative descriptive approach was employed. Data were collected through in-depth interviews, participant observation, and document analysis. Data were analyzed using a qualitative descriptive method. The findings indicate that: (1) teacher performance at MI Tarbiyatusshibyan is good, with teachers performing professionally in accordance with their duties and responsibilities; (2) the Madrasah Committee has implemented several performance indicators as advisors, supporters, controllers, and mediators, although some indicators remain unfulfilled; and (3) the Committee’s role in enhancing teacher performance is effective. This study highlights the importance of the Madrasah Committee in supporting teacher performance and provides a reference for improving educational quality through effective school governance.